(untitled) (The Peerian Journal, 2022)
First of all, if we talk about the field of sports itself, its set of laws, at present in our country the field of law called "Sports Law" is not developed in a uniform way. This area is regulated in conjunction with other areas of law. This article discusses when and how the sources and laws of sports law can be applied when concluding mixed sports contracts. As mentioned above, there are no single sources and laws of "sports law". It is understood that the conclusion of mixed sports contracts also applies to the principles of civil law, labor law, administrative and public law, special rules, private international law, the doctrine of restriction of trade in relation to general law, criminal law and trade.